Sikap Bangga Berbahasa Indonesia Yang Ditujukan Dalam Caption Instagram - Dinda Syakira; Shakila Mutia; Mayla Awaliah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
The study was to analyze the phenomenon of Indonesian use in caption of instagram that expressed a proud attitude toward Indonesia's cultural identity. Through a qualitative approach with content analysis, the article explored how the use of Indonesian in instagram caption reflects pride in local cultural heritage and values. The study involves analysis of caption of various types of instagram accounts, ranging from personal accounts to individual or influencer active in Indonesian. With a focus on linguistic, social, and cultural aspects, the study aims to understand how the use of language in instagram caption can serve asa representation of a strong national identity attitude and how it can affect user perception and interactions of the content. The findings of this study are expected to provide insight into the role of language in strengthening and promoting pride in Indonesia's cultural identity in context of social media. In the study, the methods we take are qualitative methods, we do data processing through questionnaire charging and the results show that people are already convinced in their Indonesian prideful attitude, but implementation suggests 70%. Rest shows some of our people don't really use instagram that much.